To Asses Factors Influencing and Practice of Early Initiation of Breast Feeding - Rasul, Noreen; Afzal, Sidra; Ijaz, Sara (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Early initiation of breast feeding that is breast feed given within first hour of birth prevents newborn from hypothermia, hypoglycemia and infections. It increases bonding with mother and promotes exclusive breast feeding. Objectives: To assess the factors influencing the mothers for early initiation of breast feeding and how much mothers practice it. Material and Methods: It was a retrospective study conducted at Pak Red Crescent Medical and Dental College, Dina Nath. The study was in form of questionnaire interview taken from delivered women including caesarean section and spontaneous vaginal delivery 293 and 57 women from out-patient department. Total number of women were 350. Duration of study was six months from 1 July 2021 to 31 December 2021. The influencing factors of early initiation of breast feeding and practice of giving milk within an hour after birth was assessed. Results: In our study percentage of early initiation of breast feeding was 13.4%. Maximum age for breast feeding was between 25 to 35 years that is 48.5% and regarding parity maximum in Para2 to 3 had 40%. The women who were willing for breastfeeding within first hour of birth had family support 26.2%, support by doctors or nurses 16.5% and 2% got counselling in antenatal period. Regarding factors that decrease EIBF, 53.4% women failed to initiate breast fed in first hour after birth due to pain, caesarean section under general anesthesia3.1%, discomfort due to episiotomy 6.2% and 10.5% babies were referred to neonatal unit immediately after birth due to danger signs. Conclusion: Counselling of mothers in antenatal period, improving counselling skills of health providers and strengthening community based support are likely to improve early initiation of breast feeding.